Enhancing Madura’s Tourism Potential: Financial Inclusion, Digital Technology, and the Moderating Effect of Digital Literacy - Amaniyah, Evaliati; Samsuki; Susandini, Aprilina (Jurnal Ilmiah Manajemen Kesatuan, 2025)
Tourism plays a vital role in regional economic growth and community empowerment, particularly in island regions such as Madura, where abundant coastal and marine resources hold significant potential for sustainable tourism development. This study aims to analyse how financial inclusion and the use of digital technology can promote the development of tourism potential in Madura, with digital literacy as a moderating variable. Data was obtained through a survey of tourism stakeholders and related MSMEs in the Madura region. The analysis technique used was Partial Least Squares Structural Equation Modelling (PLS-SEM). The results indicate that financial inclusion and digital technology have a positive and significant impact on tourism potential development. Digital literacy also has a direct positive impact on tourism potential; however, its role as a moderating variable yields varied results. Digital literacy does not significantly moderate the relationship between financial inclusion and tourism potential, while in the relationship between digital technology and tourism potential, digital literacy negatively moderates the relationship.  This study provides policy implications for local governments and financial institutions in expanding targeted financial access and digital education to strengthen the local economy through tourism.